A jelzáloghitelezés és a Családi Otthonteremtési Kedvezmény - Kelemen Adrienn (2017)
The main issue that I am dealing with in my thesis is mortgages, state initiatives, and the Family Housing Allowance (CSOK). During my internship at Lövő és Vidéke Takarék-szövetkezet (mutual savings bank), I had the chance to get to know more about the conditions and importance, as well as the significance, of their utilization. As the majority opt for either the mortgage or the housing allowance opportunities to home ownership, its increasingly vital impact led me to myconclusions. On the other hand, as an intern I have gathered great insight dealing in these matters. These processes included all the essential steps such as becoming eligible for a loan, scoring applicant’s credit or loan proposals. Being absorbed in the above mentioned procedures helped me get a thorough insight into understanding the complexity of CSOK. It is also vital to have all the necessary documents sent in flawlessly and the charts for client classification filled out properly. The next part in my thesis focuses on the key terminology based on the current scientific literature on mortgages alongside a practical overview on the approval procedures of Takarék Otthon Hitel. The third section presents the Hungarian home ownership programs along with a brief history and then examines the conditions, the range of future client base, benefit rates as well as the fluidization of the Family Housing Allowance. A further analysis on tax cre-dit would conclude the dissertation on the significance of such initiative programs. In conclusion, my findings will give an account based on the overall response to the question about people’s awareness of these programs and help me understand their significance even better. The research also contributed to get a broader picture of people’s general opinion about such initiatives, their misinterpretations relating to CSOK and worries about starting a family. Besides all the results concluded from the questionnaire, I also emphasized giving an account of the problematic matters I experienced during my internship that arose along with my suggestions.